Polyaniline-based composite filler doped pervaporation membrane synthesized and modified by template-induced MOFs (Metal-Organic Frameworks) as well as preparation method and application of pervaporation membrane
The preparation method of the permeable vaporized film doped with polyaniline composite filler modified by induced MOFs synthesis through template induced, solves the poor compatibility and agglomeration problems of MOFs materials when doped in the film, improves the separation performance of the film and reduces the cost, and achieves efficient permeable alcohol separation of alcohol and water mixtures.
Patent Information
- Application Number
- CN202411600385.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The existing MOFs materials have problems such as poor compatibility and easy agglomeration when doped in the film, which limits the performance of the film. Moreover, the MOFs materials are expensive, which is not conducive to the reduction of costs.
The preparation method of the permeable vaporized film doped with polyaniline composite filler-doped polyaniline sheets by induced MOFs by template induced MOFs, MOFs were synthesized and modified with silane coupling agent, and hydrophobic modification was improved to improve the dispersion and compatibility of MOFs in the film.
The separation performance of the membrane is improved, and the problem of poor agglomeration and compatibility of MOFs materials in the membrane is solved, while reducing costs and achieving efficient permeable alcohol separation of alcohol and water mixtures.
Smart Images

Figure HDA0005128143050000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional membranes and preparation and separation applications thereof, and specifically relates to a pervaporation membrane doped with a polyaniline-based composite filler modified by template-induced MOFs synthesis, and a preparation method and application thereof. Background Art
[0002] Mixed matrix membranes are recognized as one of the important ways to solve the current difficulties encountered in pervaporation membrane separation of alcohol and water mixtures. The most popular filler at present is metal organic framework (MOFs) material that has both organic and inorganic properties. However, MOFs materials still have some inevitable problems: (1) MOFs materials themselves are easy to agglomerate, which greatly limits their loading amount in the membrane and thus limits the performance of the membrane; (2) MOFs have poor compatibility with polymer matrices, which greatly affects the separation performance of the membrane; (3) MOFs materials are expensive, which is not conducive to cost reduction.
[0003] Therefore, how to solve the above problems better and faster has become a hot topic of research nowadays. One of the more recognized ideas is to compound MOFs materials with other materials to prepare composite fillers and then use them in the preparation of pervaporation membranes. The advantage of this solution is that it not only solves the problem of easy agglomeration of MOFs materials themselves and the problem of high cost, but also cleverly combines the advantages of the two materials, further enhancing the separation performance of the composite membrane.
[0004] In previous studies, combining MOFs with two-dimensional materials can not only solve the problems existing in MOFs themselves, but also give full play to the advantages of both, and comprehensively enhance the separation performance of the membrane. Therefore, the present invention uses hydrophobic polyethylene glycol-modified polyaniline sheets as templates to induce the synthesis of MOFs to prepare a new composite material for the preparation of mixed matrix membranes, and for the separation of alcohol-water solutions. Summary of the invention
[0005] In order to overcome the problems of poor compatibility and easy agglomeration when MOFs materials are doped in the prior art, the present invention provides a pervaporation membrane doped with a polyaniline-based composite filler modified by template-induced MOFs synthesis, and a preparation method and application thereof.
[0006] The technical solution of the present invention is as follows:
[0007] A template-induced MOFs synthesis-modified polyaniline-based composite filler-doped pervaporation membrane is prepared as follows:
[0008] S1: Disperse polyaniline sheets uniformly in deionized water, add polyethylene glycol solid, react at room temperature for 5 to 10 hours (preferably 8 hours), filter, wash (with deionized water), and dry (50°C, 12 hours) to obtain polyethylene glycol-modified polyaniline sheets;
[0009] The mass ratio of deionized water to polyaniline sheet is 50 to 2000:1, preferably 800:1;
[0010] The mass ratio of polyaniline sheet to polyethylene glycol solid is 1:0.1-10, preferably 1:2;
[0011] The molecular weight of the polyethylene glycol solid is between 10,000 and 40,000, preferably 20,000;
[0012] S2: Add polyethylene glycol-modified polyaniline sheets to solvent A, mix them by ultrasonication (30 min), then add metal source and stir evenly (30 min), which is recorded as solution A; add ligand to solvent B, stir and dissolve, which is recorded as solution B; pour solution B into solution A, stir and react at room temperature, then filter, wash and dry (80°C, 12h), then add the obtained solid product to the pre-hydrolysis solution of silane coupling agent, stir and react, then filter, wash with water and dry (80°C, 12h) to obtain MOFs-modified polyaniline;
[0013] In this step, the metal source reacts with the ligand to synthesize MOFs, which are grown in situ on the polyethylene glycol-modified polyaniline sheet, and then hydrophobically modified by a silane coupling agent to obtain MOFs-modified polyaniline; the reaction time of MOFs synthesis, the solvent for MOFs synthesis, and the modification time of the silane coupling agent can be determined according to the selection of the material itself;
[0014] MOFs are selected from ZIF-8, ZIF-90, ZIF-67, ZIF-91, ZIF-71, MOF-808, MOF-199, etc.;
[0015] The mass ratio of polyethylene glycol-modified polyaniline sheet, metal source and solvent A is 1:5-15:200-1500;
[0016] The mass ratio of ligand to solvent B is 1:200-1500;
[0017] The pre-hydrolysis solution of the silane coupling agent is composed of: silane coupling agent, water, and ethanol in a mass ratio of 0.1-5:1-10:80-99;
[0018] The silane coupling agent is selected from γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, anilinemethyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, etc.
[0019] In this step, "solvent A", "solvent B", "solution A", and "solution B" have no special meanings, and are marked as "A" and "B" only to distinguish the solvents or solutions involved in different operations;
[0020] S3: Disperse PDMS (polydimethylsiloxane) evenly in n-heptane, add the polyaniline modified by MOFs obtained in S2, a crosslinking agent, and a catalyst, disperse evenly, and let stand (10 to 30 minutes) to obtain a casting solution; spin-coat the casting solution on a PVDF (polyvinylidene fluoride) membrane, and after drying, obtain the template-induced MOFs synthesis-modified polyaniline-based composite filler doped pervaporation membrane;
[0021] The volume mass ratio of n-heptane to PDMS is 2.9 to 14.6:1, mL / g; preferably 5.85:1, mL / g;
[0022] The mass ratio of PDMS, crosslinking agent, catalyst and MOFs-modified polyaniline is 1:0.05-0.2:0.005-0.03:0.01-0.3, preferably 1:0.1:0.01:0.2;
[0023] Specifically, the crosslinking agent is ethyl orthosilicate, the catalyst is dibutyltin dilaurate, and the viscosity of PDMS at 25° C. is 50,000 cst;
[0024] The molecular weight cutoff of the PVDF membrane is 20,000 to 100,000. The PVDF membrane is pretreated as follows before use: the PVDF membrane is soaked in an ethanol aqueous solution with a volume fraction of 20 to 70% (preferably 50%) for 3 to 6 hours, and then taken out and rinsed with deionized water to complete the pretreatment of the PVDF membrane (placed in deionized water for standby use);
[0025] When making the membrane, the amount of the casting solution on the PVDF membrane is 0.05-0.3 g / cm 2 , preferably 0.1 g / cm 2 .
[0026] In the present invention, the preparation method of the polyaniline sheet is as follows:
[0027] Aniline is dissolved in 0.2-2M (preferably 1M) hydrochloric acid to obtain an aniline solution; at 0-5°C (preferably 0-2°C), an aqueous ammonium persulfate solution is (quickly) added to the aniline solution, stirred for 0.5-2h (preferably 1h), filtered, the filter cake is washed with water and methanol in turn (until the filtrate is colorless), dried, the obtained solid is stirred in 3-15wt% (preferably 5wt%) ammonia aqueous solution for 16-30h (preferably 24h), filtered, the filter cake is washed with water and methanol in turn, and dried to obtain the polyaniline sheet;
[0028] The molar ratio of aniline to ammonium persulfate is 1.5 to 2.8:1, preferably 2:1;
[0029] The concentration of aniline in the aniline solution is 0.005 to 2 M, preferably 1 M;
[0030] The concentration of the ammonium persulfate aqueous solution is 0.002 to 2 M, preferably 0.5 M;
[0031] Specifically, the aniline solution and the ammonium persulfate aqueous solution are cooled to 0-5° C. and then mixed;
[0032] The volume mass ratio of the ammonia solution to the solid is 50 to 500:1, mL / g; preferably 100:1, mL / g.
[0033] The template-induced MOFs synthesis-modified polyaniline-based composite filler-doped pervaporation membrane of the present invention can be used for the pervaporation separation of alcohol-water mixtures; the alcohol in the alcohol-water mixture is, for example, one or both of butanol and ethanol.
[0034] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0035] (1) Polyaniline is a two-dimensional material. Multilayers facilitate the permeation of alcohol and extend the path of water molecules, thereby enhancing the separation performance of the membrane. In addition, polyaniline is a hydrophobic material, which can further enhance the separation performance of the membrane.
[0036] (2) Different MOF materials can be selected during the filler compounding process. On the one hand, the advantages of MOF porous materials can be brought into play, such as the property of preferential alcohol permeation; on the other hand, the dispersibility of MOF materials can be improved and the agglomeration of MOF materials in PDMS can be inhibited. This can improve the loading of fillers in the membrane and make it easier to obtain high-performance, uniform and defect-free mixed matrix pervaporation membranes.
[0037] (3) The hydrophobically modified composite filler has abundant hydrophobic organic functional groups, which effectively enhances the compatibility between the filler and PDMS. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 : Diagram of the pervaporation apparatus. DETAILED DESCRIPTION
[0039] The present invention is further described below by means of specific embodiments, but the protection scope of the present invention is not limited thereto.
[0040] In the following embodiments,
[0041] The viscosity of polydimethylsiloxane (PDMS) is 50000cst, the model is XC-107-50000, and the manufacturer is Jinan Xingchi Chemical Co., Ltd.
[0042] Embodiment 1:
[0043] (1) Treatment of PVDF bottom membrane: Soak the PVDF bottom membrane with a molecular weight cutoff of 50,000 in a mixed solution of 50% by volume ethanol / water for 5 h, then take it out and rinse it with deionized water, and then place it in deionized water for use.
[0044] (2) Synthesis of layered polyaniline: Add 9.313 g of aniline to 100 mL of 1 M hydrochloric acid, stir for 30 min to mix evenly, record as solution A, and set aside. Take 11.41 g of ammonium persulfate and add it to 100 mL of deionized water, stir for 30 min to dissolve and mix evenly, record as solution B, and set aside. After solution A and solution B are cooled to 0-5°C respectively, quickly pour solution B into solution A. Keep the temperature range between 0-2°C and stir for 1 hour. After the reaction is completed, filter, wash with water and methanol until the filtrate is colorless, and dry in an oven at 80°C for 12 hours to obtain layered polyaniline powder-doped state (doped HCl molecules, layered polyaniline is a type of polyaniline morphology, which is related to the raw material ratio and experimental conditions during synthesis). Then, 5 g of the layered polyaniline powder-doped state was added to 500 mL of 5 wt % ammonia solution, stirred for 24 h, filtered, washed with water and methanol twice in sequence, and dried in an oven at 80° C. for 12 h to obtain layered polyaniline.
[0045] (3) Preparation of polyethylene glycol-modified polyaniline: 0.1 g of polyaniline flakes were uniformly dispersed in 80 g of deionized water, and 0.2 g of polyethylene glycol solid was added. The mixture was reacted at room temperature for 8 h, and then filtered, washed with deionized water for 3 times, and dried in an oven at 50° C. for 12 h to obtain polyethylene glycol-modified polyaniline.
[0046] (4) ZIF-90 modified polyaniline: 0.1 g of polyethylene glycol modified polyaniline sheet material was added to 50 mL of methanol, and stirred evenly after ultrasonic treatment for 30 min. Then, 1 g of zinc nitrate hexahydrate was added and stirred for 30 min. The mixture was set aside as solution A. 1.7 g of 2-imidazole carboxaldehyde was weighed and added to 50 mL of N,N-dimethylformamide, and stirred and dissolved. The mixture was set aside as solution B. Subsequently, solution B was poured into solution A, stirred at room temperature for 1 h, filtered and washed with methanol 3 times, and dried in an oven at 80 °C for 12 h to obtain ZIF-90 pre-modified polyaniline. Finally, 0.2 g of this material was added to 50 mL of pre-hydrolysis solution (1 wt% KH550, 2 wt% water, 97 wt% ethanol), stirred at room temperature for 5 h, filtered and washed with water 3 times, and dried in an oven at 80 °C for 12 h to obtain ZIF-90 modified polyaniline.
[0047] (5) Preparation of template-induced ZIF-90 synthesis-modified polyaniline-based pervaporation membrane: 0.855 g of polydimethylsiloxane (PDMS) was added to 5 mL of n-heptane, stirred at room temperature for 30 min, then 0.128 g of ZIF-90-modified polyaniline powder was added and stirred for 30 min; the steps of stirring for 30 min and ultrasonication for 30 min were repeated for 3 h; then 0.0855 g of cross-linking agent tetraethyl orthosilicate was added and stirred for 15 min, 0.0086 g of catalyst dibutyltin dilaurate was added and stirred for 30 min, and after standing for 20 min (standing to remove bubbles), 2 mL of the obtained casting solution was taken and a membrane was formed on the above-mentioned PVDF membrane (radius 2 cm disc) by spin coating, and dried in an oven at 80°C for 12 h to obtain a template-induced ZIF-90 synthesis-modified polyaniline-based pervaporation membrane.
[0048] The permeation flux of the polyaniline-based pervaporation membrane modified by template-induced ZIF-90 synthesis was 2777 g / m at 40°C, 5 wt% ethanol / water, flow rate 400 mL / min, and filtration vacuum less than 200 Pa. 2 h, the separation factor is 15.1.
[0049] Embodiment 2:
[0050] (1) Treatment of PVDF bottom membrane: Soak the PVDF bottom membrane with a molecular weight cutoff of 50,000 in a mixed solution of 50% by volume ethanol / water for 5 h, then take it out and rinse it with deionized water, and then place it in deionized water for use.
[0051] (2) Synthesis of layered polyaniline: Add 9.313 g of aniline to 100 mL of 1 M hydrochloric acid, stir for 30 min to mix evenly, record as solution A, and set aside. Take 11.41 g of ammonium persulfate and add it to 100 mL of deionized water, stir for 30 min to dissolve and mix evenly, record as solution B, and set aside. After solution A and solution B are cooled to 0-5°C respectively, quickly pour solution B into solution A. Keep the temperature range between 0-2°C and stir for 1 hour. After the reaction is completed, filter, wash with water and methanol until the filtrate is colorless, and dry in an oven at 80°C for 12 hours to obtain layered polyaniline powder-doped state (doped HCl molecules, layered polyaniline is a type of polyaniline morphology, which is related to the raw material ratio and experimental conditions during synthesis). Then, 5 g of the layered polyaniline powder-doped state was added to 500 mL of 5 wt % ammonia solution, stirred for 24 h, filtered, washed with water and methanol twice in sequence, and dried in an oven at 80° C. for 12 h to obtain layered polyaniline.
[0052] (3) Preparation of polyethylene glycol-modified polyaniline: 0.1 g of polyaniline flakes were uniformly dispersed in 80 g of deionized water, and 0.2 g of polyethylene glycol solid was added. The mixture was reacted at room temperature for 8 h, and then filtered, washed with deionized water for 3 times, and dried in an oven at 50° C. for 12 h to obtain polyethylene glycol-modified polyaniline.
[0053] (4) ZIF-90 modified polyaniline: 0.1 g of polyethylene glycol modified polyaniline sheet material was added to 50 mL of methanol, and stirred evenly after ultrasonic treatment for 30 min. Then, 1 g of zinc nitrate hexahydrate was added and stirred for 30 min. The mixture was set aside as solution A. 1.7 g of 2-imidazole carboxaldehyde was weighed and added to 50 mL of N,N-dimethylformamide, and stirred and dissolved. The mixture was set aside as solution B. Subsequently, solution B was poured into solution A, stirred and reacted at room temperature for 1 h, filtered and washed with methanol 3 times, and dried in an oven at 80 °C for 12 h to obtain ZIF-90 pre-modified polyaniline. Finally, 0.2 g of this material was added to 50 mL of pre-hydrolysis solution (1 wt% KH560, 2 wt% water, 97 wt% ethanol), stirred and reacted at 45 °C for 5 h, filtered and washed with water 3 times, and dried in an oven at 80 °C for 12 h to obtain ZIF-90 modified polyaniline.
[0054] (5) Preparation of template-induced ZIF-90 synthesis-modified polyaniline-based pervaporation membrane: 0.855 g of polydimethylsiloxane (PDMS) was added to 5 mL of n-heptane, stirred at room temperature for 30 min, then 0.128 g of ZIF-90-modified polyaniline powder was added and stirred for 30 min; the steps of stirring for 30 min and ultrasonication for 30 min were repeated for 3 h; then 0.0855 g of cross-linking agent tetraethyl orthosilicate was added and stirred for 15 min, 0.0086 g of catalyst dibutyltin dilaurate was added and stirred for 30 min, and after standing for 20 min (standing to remove bubbles), 2 mL of the obtained casting solution was taken and a membrane was formed on the above-mentioned PVDF membrane (radius 2 cm disc) by spin coating, and dried in an oven at 80°C for 12 h to obtain a template-induced ZIF-90 synthesis-modified polyaniline-based pervaporation membrane.
[0055] The permeation flux of the polyaniline-based pervaporation membrane modified by template-induced ZIF-90 synthesis was 2210 g / m at 40 ° C, 5 wt% ethanol / water, flow rate 400 mL / min, and filtration vacuum less than 200 Pa. 2 h, the separation factor is 17.8.
[0056] Embodiment 3:
[0057] (1) Treatment of PVDF bottom membrane: Soak the PVDF bottom membrane with a molecular weight cutoff of 50,000 in a mixed solution of 50% by volume ethanol / water for 5 h, then take it out and rinse it with deionized water, and then place it in deionized water for use.
[0058] (2) Synthesis of layered polyaniline: Add 9.313 g of aniline to 100 mL of 1 M hydrochloric acid, stir for 30 min to mix evenly, record as solution A, and set aside. Take 11.41 g of ammonium persulfate and add it to 100 mL of deionized water, stir for 30 min to dissolve and mix evenly, record as solution B, and set aside. After solution A and solution B are cooled to 0-5°C respectively, quickly pour solution B into solution A. Keep the temperature range between 0-2°C and stir for 1 hour. After the reaction is completed, filter, wash with water and methanol until the filtrate is colorless, and dry in an oven at 80°C for 12 hours to obtain layered polyaniline powder-doped state (doped HCl molecules, layered polyaniline is a type of polyaniline morphology, which is related to the raw material ratio and experimental conditions during synthesis). Then, 5 g of the layered polyaniline powder-doped state was added to 500 mL of 5 wt % ammonia solution, stirred for 24 h, filtered, washed with water and methanol twice in sequence, and dried in an oven at 80° C. for 12 h to obtain layered polyaniline.
[0059] (3) Preparation of polyethylene glycol-modified polyaniline: 0.1 g of polyaniline flakes were uniformly dispersed in 80 g of deionized water, and 0.2 g of polyethylene glycol solid was added. The mixture was reacted at room temperature for 8 h, and then filtered, washed with deionized water for 3 times, and dried in an oven at 50° C. for 12 h to obtain polyethylene glycol-modified polyaniline.
[0060] (4) ZIF-8 modified polyaniline: 0.1 g of polyethylene glycol modified polyaniline sheet material was added to 50 mL of methanol, and stirred evenly after ultrasonic treatment for 30 min. Then, 1 g of zinc nitrate hexahydrate was added and stirred for 30 min. The mixture was set aside as solution A. 2.22 g of 2-methylimidazole was weighed and added to 50 mL of methanol. The mixture was stirred and dissolved and set aside as solution B. Subsequently, solution B was poured into solution A, stirred at room temperature for 40 min, filtered and washed with methanol 3 times, and dried in an oven at 80°C for 12 h to obtain ZIF-8 preliminarily modified polyaniline. Finally, 0.2 g of this material was added to 50 mL of pre-hydrolysis solution (1 wt% KH550, 2 wt% water, 97 wt% ethanol), stirred at room temperature for 5 h, filtered and washed with water 3 times, and dried in an oven at 80°C for 12 h to obtain ZIF-8 modified polyaniline.
[0061] (5) Preparation of template-induced ZIF-8 synthesis-modified polyaniline-based pervaporation membrane: 0.855 g of polydimethylsiloxane (PDMS) was added to 5 mL of n-heptane, and stirred at room temperature for 30 min. Then, 0.154 g of ZIF-8-modified polyaniline powder was added and stirred for 30 min. After that, the steps of stirring for 30 min and ultrasonication for 30 min were repeated for 3 h. Then, 0.0855 g of cross-linking agent tetraethyl orthosilicate was added and stirred for 15 min. Then, 0.0086 g of catalyst dibutyltin dilaurate was added and stirred for 30 min. After standing for 20 min (standing to remove bubbles), 2 mL of the obtained casting solution was taken and a membrane was formed on the above-mentioned PVDF membrane (radius 2 cm disc) by spin coating, and dried in an oven at 80°C for 12 h. Finally, a template-induced ZIF-8 synthesis-modified polyaniline-based pervaporation membrane was obtained.
[0062] The permeation flux of the obtained template-induced ZIF-8 synthesized modified polyaniline-based pervaporation membrane at 40°C, 1 wt% butanol / water, flow rate 400 mL / min, and filtration vacuum less than 200 Pa was 2611 g / m 2 h, the separation factor is 58.3; the permeation flux is 2393 g / m at 40 ° C, 5 wt% ethanol / water, flow rate 400 mL / min, and filtration vacuum less than 200 Pa. 2 h, the separation factor is 17.4.
[0063] Embodiment 4:
[0064] (1) Treatment of PVDF bottom membrane: Soak the PVDF bottom membrane with a molecular weight cutoff of 50,000 in a mixed solution of 50% by volume ethanol / water for 5 h, then take it out and rinse it with deionized water, and then place it in deionized water for use.
[0065] (2) Synthesis of layered polyaniline: Add 9.313 g of aniline to 100 mL of 1 M hydrochloric acid, stir for 30 min to mix evenly, record as solution A, and set aside. Take 11.41 g of ammonium persulfate and add it to 100 mL of deionized water, stir for 30 min to dissolve and mix evenly, record as solution B, and set aside. After solution A and solution B are cooled to 0-5°C respectively, quickly pour solution B into solution A. Keep the temperature range between 0-2°C and stir for 1 hour. After the reaction is completed, filter, wash with water and methanol until the filtrate is colorless, and dry in an oven at 80°C for 12 hours to obtain layered polyaniline powder-doped state (doped HCl molecules, layered polyaniline is a type of polyaniline morphology, which is related to the raw material ratio and experimental conditions during synthesis). Then, 5 g of the layered polyaniline powder-doped state was added to 500 mL of 5 wt % ammonia solution, stirred for 24 h, filtered, washed with water and methanol twice in sequence, and dried in an oven at 80° C. for 12 h to obtain layered polyaniline.
[0066] (3) Preparation of polyethylene glycol-modified polyaniline: 0.1 g of polyaniline flakes were uniformly dispersed in 80 g of deionized water, and 0.2 g of polyethylene glycol solid was added. The mixture was reacted at room temperature for 8 h, and then filtered, washed with deionized water for 3 times, and dried in an oven at 50° C. for 12 h to obtain polyethylene glycol-modified polyaniline.
[0067] (4) ZIF-8 modified polyaniline: 0.1 g of polyethylene glycol modified polyaniline sheet material was added to 50 mL of water, and stirred evenly after ultrasonic treatment for 30 min. Then, 1 g of zinc nitrate hexahydrate was added and stirred for 30 min. The mixture was set aside as solution A. 2.22 g of 2-methylimidazole was weighed and added to 50 mL of water. The mixture was stirred and dissolved and set aside as solution B. Subsequently, solution B was poured into solution A, stirred at room temperature for 40 min, filtered and washed with water 3 times, and dried in an oven at 80°C for 12 h to obtain ZIF-8 preliminarily modified polyaniline. Finally, 0.2 g of this material was added to 50 mL of pre-hydrolysis solution (1 wt% KH550, 2 wt% water, 97 wt% ethanol), stirred at room temperature for 5 h, filtered and washed with water 3 times, and dried in an oven at 80°C for 12 h to obtain ZIF-8 modified polyaniline.
[0068] (5) Preparation of template-induced ZIF-8 synthesis-modified polyaniline-based pervaporation membrane: 0.855 g of polydimethylsiloxane (PDMS) was added to 5 mL of n-heptane, and stirred at room temperature for 30 min. Then, 0.154 g of ZIF-8-modified polyaniline powder was added and stirred for 30 min. After that, the steps of stirring for 30 min and ultrasonication for 30 min were repeated for 3 h. Then, 0.0855 g of cross-linking agent tetraethyl orthosilicate was added and stirred for 15 min. Then, 0.0086 g of catalyst dibutyltin dilaurate was added and stirred for 30 min. After standing for 20 min (standing to remove bubbles), 2 mL of the obtained casting solution was taken and a membrane was formed on the above-mentioned PVDF membrane (radius 2 cm disc) by spin coating, and dried in an oven at 80°C for 12 h. Finally, a template-induced ZIF-8 synthesis-modified polyaniline-based pervaporation membrane was obtained.
[0069] The permeation flux of the obtained template-induced ZIF-8 synthesized modified polyaniline-based pervaporation membrane at 40°C, 1wt% butanol / water, flow rate 400mL / min, and filtration vacuum less than 200 Pa was 3503g / m 2 h, the separation factor is 49.2; the permeation flux is 2819 g / m at 40 ° C, 5 wt% ethanol / water, flow rate 400 mL / min, and filtration vacuum less than 200 Pa. 2 h, the separation factor is 14.8.
[0070] Embodiment 5:
[0071] (1) Treatment of PVDF bottom membrane: Soak the PVDF bottom membrane with a molecular weight cutoff of 50,000 in a mixed solution of 50% by volume ethanol / water for 5 h, then take it out and rinse it with deionized water, and then place it in deionized water for use.
[0072] (2) Synthesis of layered polyaniline: Add 9.313 g of aniline to 100 mL of 1 M hydrochloric acid, stir for 30 min to mix evenly, record as solution A, and set aside. Take 11.41 g of ammonium persulfate and add it to 100 mL of deionized water, stir for 30 min to dissolve and mix evenly, record as solution B, and set aside. After solution A and solution B are cooled to 0-5°C respectively, quickly pour solution B into solution A. Keep the temperature range between 0-2°C and stir for 1 hour. After the reaction is completed, filter, wash with water and methanol until the filtrate is colorless, and dry in an oven at 80°C for 12 hours to obtain layered polyaniline powder-doped state (doped HCl molecules, layered polyaniline is a type of polyaniline morphology, which is related to the raw material ratio and experimental conditions during synthesis). Then, 5 g of the layered polyaniline powder-doped state was added to 500 mL of 5 wt % ammonia solution, stirred for 24 h, filtered, washed with water and methanol twice in sequence, and dried in an oven at 80° C. for 12 h to obtain layered polyaniline.
[0073] (3) Preparation of polyethylene glycol-modified polyaniline: 0.1 g of polyaniline flakes were uniformly dispersed in 80 g of deionized water, and 0.2 g of polyethylene glycol solid was added. The mixture was reacted at room temperature for 8 h, and then filtered, washed with deionized water for 3 times, and dried in an oven at 50° C. for 12 h to obtain polyethylene glycol-modified polyaniline.
[0074] (4) ZIF-67 modified polyaniline: 0.1 g of polyethylene glycol modified polyaniline sheet material was added to 50 mL of methanol, and stirred evenly after ultrasonic treatment for 30 min. Then, 1 g of cobalt nitrate hexahydrate was added and stirred for 30 min. The mixture was set aside as solution A. 2.24 g of 2-methylimidazole was weighed and added to 50 mL of methanol. The mixture was stirred and dissolved and set aside as solution B. Subsequently, solution B was poured into solution A, stirred at room temperature for 45 min, filtered and washed with methanol 3 times, and dried in an oven at 80°C for 12 h to obtain ZIF-67 modified polyaniline. Finally, 0.2 g of this material was added to 50 mL of pre-hydrolysis solution (1 wt% KH590, 2 wt% water, 97 wt% ethanol), stirred at 60°C for 5 h, filtered and washed with water 3 times, and dried in an oven at 80°C for 12 h to obtain ZIF-67 modified polyaniline.
[0075] (5) Preparation of template-induced ZIF-67 synthesis-modified polyaniline-based pervaporation membrane: 0.855 g of polydimethylsiloxane (PDMS) was added to 5 mL of n-heptane, stirred at room temperature for 30 min, then 0.0855 g of ZIF-67-modified polyaniline powder was added and stirred for 30 min; the steps of stirring for 30 min and ultrasonication for 30 min were repeated for 3 h; then 0.0855 g of cross-linking agent tetraethyl orthosilicate was added and stirred for 15 min, 0.0086 g of catalyst dibutyltin dilaurate was added and stirred for 30 min, and after standing for 20 min (standing to remove bubbles), 2 mL of the obtained casting solution was taken and a membrane was formed on the above-mentioned PVDF membrane (radius 2 cm disc) by spin coating, and dried in an oven at 80°C for 12 h to obtain a template-induced ZIF-67 synthesis-modified polyaniline-based pervaporation membrane.
[0076] The permeation flux of the polyaniline-based pervaporation membrane modified by template-induced ZIF-67 synthesis was 2579 g / m at 40 °C, 1 wt% butanol / water, flow rate 400 mL / min, and filtration vacuum less than 200 Pa. 2 h, separation factor is 53;
[0077] Embodiment 6:
[0078] (1) Treatment of PVDF bottom membrane: Soak the PVDF bottom membrane with a molecular weight cutoff of 50,000 in a mixed solution of 50% by volume ethanol / water for 5 h, then take it out and rinse it with deionized water, and then place it in deionized water for use.
[0079] (2) Synthesis of layered polyaniline: Add 9.313 g of aniline to 100 mL of 1 M hydrochloric acid, stir for 30 min to mix evenly, record as solution A, and set aside. Take 11.41 g of ammonium persulfate and add it to 100 mL of deionized water, stir for 30 min to dissolve and mix evenly, record as solution B, and set aside. After solution A and solution B are cooled to 0-5°C respectively, quickly pour solution B into solution A. Keep the temperature range between 0-2°C and stir for 1 hour. After the reaction is completed, filter, wash with water and methanol until the filtrate is colorless, and dry in an oven at 80°C for 12 hours to obtain layered polyaniline powder-doped state (doped HCl molecules, layered polyaniline is a type of polyaniline morphology, which is related to the raw material ratio and experimental conditions during synthesis). Then, 5 g of the layered polyaniline powder-doped state was added to 500 mL of 5 wt % ammonia solution, stirred for 24 h, filtered, washed with water and methanol twice in sequence, and dried in an oven at 80° C. for 12 h to obtain layered polyaniline.
[0080] (3) Preparation of polyethylene glycol-modified polyaniline: 0.1 g of polyaniline flakes were uniformly dispersed in 80 g of deionized water, and 0.2 g of polyethylene glycol solid was added. The mixture was reacted at room temperature for 8 h, and then filtered, washed with deionized water for 3 times, and dried in an oven at 50° C. for 12 h to obtain polyethylene glycol-modified polyaniline.
[0081] (4) ZIF-71 modified polyaniline: 0.1 g of polyethylene glycol modified polyaniline sheet material was added to 50 mL of methanol, and stirred evenly after ultrasonic treatment for 30 min. Then, 1 g of zinc acetate dihydrate was added and stirred for 30 min. The mixture was set aside as solution A. 2.5 g of 4,5-dichloroimidazole was weighed and added to 50 mL of methanol. The mixture was stirred and dissolved and set aside as solution B. Subsequently, solution B was slowly added dropwise to solution A, and the mixture was stirred at room temperature for 120 min. The mixture was filtered and washed with methanol for 3 times, and dried in an oven at 80 °C for 12 h to obtain polyaniline preliminarily modified with ZIF-67. Finally, 0.2 g of the material was added to 50 mL of pre-hydrolysis solution (1 wt% KH590, 2 wt% water, 97 wt% ethanol), stirred at room temperature for 5 h, filtered and washed with water for 3 times, and dried in an oven at 80 °C for 12 h to obtain polyaniline modified with ZIF-71.
[0082] (5) Preparation of template-induced ZIF-71 synthesis-modified polyaniline-based pervaporation membrane: 0.855 g of polydimethylsiloxane (PDMS) was added to 5 mL of n-heptane, and stirred at room temperature for 30 min. Then, 0.103 g of ZIF-71-modified polyaniline powder was added and stirred for 30 min. After that, the steps of stirring for 30 min and ultrasonication for 30 min were repeated for 3 h. Then, 0.0855 g of cross-linking agent tetraethyl orthosilicate was added and stirred for 15 min. Then, 0.0086 g of catalyst dibutyltin dilaurate was added and stirred for 30 min. After standing for 20 min (standing to remove bubbles), 2 mL of the obtained casting solution was taken and a membrane was formed on the above-mentioned PVDF membrane (radius 2 cm disc) by spin coating, and dried in an oven at 80°C for 12 h. Finally, a template-induced ZIF-71 synthesis-modified polyaniline-based pervaporation membrane was obtained.
[0083] The permeation flux of the obtained template-induced ZIF-71 modified polyaniline-based pervaporation membrane at 40°C, 1 wt% butanol / water, flow rate 400 mL / min, and filtration vacuum less than 200 Pa was 2810 g / m 2 h, separation factor is 46.7;
[0084] Comparative Example 1: No MOF material
[0085] (1) Treatment of PVDF bottom membrane: Soak the PVDF bottom membrane with a molecular weight cutoff of 50,000 in a mixed solution of 50% by volume ethanol / water for 5 h, then take it out and rinse it with deionized water, and then place it in deionized water for use.
[0086] (2) Synthesis of layered polyaniline: Add 9.313 g of aniline to 100 mL of 1 M hydrochloric acid, stir for 30 min to mix evenly, record as solution A, and set aside. Take 11.41 g of ammonium persulfate and add it to 100 mL of deionized water, stir for 30 min to dissolve and mix evenly, record as solution B, and set aside. After solution A and solution B are cooled to 0-5°C respectively, quickly pour solution B into solution A. Keep the temperature range between 0-2°C and stir for 1 hour. After the reaction is completed, filter, wash with water and methanol until the filtrate is colorless, and dry in an oven at 80°C for 12 hours to obtain layered polyaniline powder-doped state (doped HCl molecules, layered polyaniline is a type of polyaniline morphology, which is related to the raw material ratio and experimental conditions during synthesis). Then, 5 g of the layered polyaniline powder-doped state was added to 500 mL of 5 wt % ammonia solution, stirred for 24 h, filtered, washed with water and methanol twice in sequence, and dried in an oven at 80° C. for 12 h to obtain layered polyaniline.
[0087] (3) Preparation of polyethylene glycol-modified polyaniline: 0.1 g of polyaniline flakes were uniformly dispersed in 80 g of deionized water, and 0.2 g of polyethylene glycol solid was added. The mixture was reacted at room temperature for 8 h, and then filtered, washed with deionized water for 3 times, and dried in an oven at 50° C. for 12 h to obtain polyethylene glycol-modified polyaniline.
[0088] (4) Silane-modified polyaniline: 0.2 g of polyethylene glycol-modified polyaniline was added into 50 mL of pre-hydrolysis solution (1 wt% KH550, 2 wt% water, 97 wt% ethanol), stirred at room temperature for 5 h, filtered and washed with water 3 times, and dried in an oven at 80° C. for 12 h to obtain silane-modified polyaniline.
[0089] (5) Preparation of silane-modified polyaniline-based pervaporation membrane: 0.855 g of polydimethylsiloxane (PDMS) was added to 5 mL of n-heptane, and stirred at room temperature for 30 min. Then, 0.154 g of silane-modified polyaniline powder was added and stirred for 30 min. Then, the steps of stirring for 30 min and ultrasonicating for 30 min were repeated for 3 h. Then, 0.0855 g of cross-linking agent tetraethyl orthosilicate was added and stirred for 15 min. Then, 0.0086 g of catalyst dibutyltin dilaurate was added and stirred for 30 min. After standing for 20 min (standing to remove bubbles), 2 mL of the obtained casting solution was taken and a membrane was formed on the above-mentioned PVDF membrane (2 cm radius disc) by spin coating, and dried in an oven at 80°C for 12 h. Finally, a silane-modified polyaniline-based pervaporation membrane was obtained.
[0090] The permeation flux of the obtained silane-modified polyaniline-based pervaporation membrane at 40°C, 1 wt% butanol / water, flow rate 400 mL / min, and filtration vacuum less than 200 Pa was 1149 g / m 2h, the separation factor is 51; the permeation flux is 1098 g / m at 40 ° C, 5 wt% ethanol / water, flow rate 400 mL / min, and filtration vacuum less than 200 Pa. 2 h, the separation factor is 13.3. (The presence of MOF provides the membrane with a certain alcohol selectivity and a large amount of flux, so the absence of porous MOF will cause a significant decrease in the flux of the composite membrane)
[0091] Comparative Example 2: No silane modification
[0092] (1) Treatment of PVDF bottom membrane: Soak the PVDF bottom membrane with a molecular weight cutoff of 50,000 in a mixed solution of 50% by volume ethanol / water for 5 h, then take it out and rinse it with deionized water, and then place it in deionized water for use.
[0093] (2) Synthesis of layered polyaniline: Add 9.313 g of aniline to 100 mL of 1 M hydrochloric acid, stir for 30 min to mix evenly, record as solution A, and set aside. Take 11.41 g of ammonium persulfate and add it to 100 mL of deionized water, stir for 30 min to dissolve and mix evenly, record as solution B, and set aside. After solution A and solution B are cooled to 0-5°C respectively, quickly pour solution B into solution A. Keep the temperature range between 0-2°C and stir for 1 hour. After the reaction is completed, filter, wash with water and methanol until the filtrate is colorless, and dry in an oven at 80°C for 12 hours to obtain layered polyaniline powder-doped state (doped HCl molecules, layered polyaniline is a type of polyaniline morphology, which is related to the raw material ratio and experimental conditions during synthesis). Then, 5 g of the layered polyaniline powder-doped state was added to 500 mL of 5 wt % ammonia solution, stirred for 24 h, filtered, washed with water and methanol twice in sequence, and dried in an oven at 80° C. for 12 h to obtain layered polyaniline.
[0094] (3) Preparation of polyethylene glycol-modified polyaniline: 0.1 g of polyaniline flakes were uniformly dispersed in 80 g of deionized water, and 0.2 g of polyethylene glycol solid was added. The mixture was reacted at room temperature for 8 h, and then filtered, washed with deionized water for 3 times, and dried in an oven at 50° C. for 12 h to obtain polyethylene glycol-modified polyaniline.
[0095] (4) ZIF-8 modified polyaniline: 0.1 g of polyethylene glycol modified polyaniline sheet material was added to 50 mL of methanol, and stirred evenly after ultrasonic treatment for 30 min. Then 1 g of zinc nitrate hexahydrate was added and stirred for 30 min. The mixture was set aside as solution A. 2.22 g of 2-methylimidazole was weighed and added to 50 mL of methanol. The mixture was stirred and dissolved and set aside as solution B. Subsequently, solution B was poured into solution A, stirred at room temperature for 40 min, filtered and washed with methanol 3 times, and dried in an oven at 80°C for 12 h to obtain ZIF-8 modified polyaniline.
[0096] (5) Preparation of template-induced ZIF-8 synthesis-modified polyaniline-based pervaporation membrane: 0.855 g of polydimethylsiloxane (PDMS) was added to 5 mL of n-heptane, and stirred at room temperature for 30 min. Then, 0.154 g of ZIF-8-modified polyaniline powder was added and stirred for 30 min. After that, the steps of stirring for 30 min and ultrasonication for 30 min were repeated for 3 h. Then, 0.0855 g of cross-linking agent tetraethyl orthosilicate was added and stirred for 15 min. Then, 0.0086 g of catalyst dibutyltin dilaurate was added and stirred for 30 min. After standing for 20 min (standing to remove bubbles), 2 mL of the obtained casting solution was taken and a membrane was formed on the above-mentioned PVDF membrane (radius 2 cm disc) by spin coating, and dried in an oven at 80°C for 12 h. Finally, a template-induced ZIF-8 synthesis-modified polyaniline-based pervaporation membrane was obtained.
[0097] The permeation flux of the polyaniline-based pervaporation membrane modified by template-induced ZIF-8 synthesis was 2937 g / m at 40 °C, 1 wt% butanol / water, flow rate 400 mL / min, and filtration vacuum less than 200 Pa. 2 h, the separation factor is 45.2; the permeation flux is 2444 g / m at 40 ° C, 5 wt% ethanol / water, flow rate 400 mL / min, and filtration vacuum less than 200 Pa. 2 h, the separation factor is 12.5. (The presence of silane modification can improve the hydrophobicity of the filler to improve the selectivity of the membrane to alcohols, and on the other hand, it grafts a large number of hydrophobic organic functional groups to the filler and enhances the compatibility between the filler and PDMS, avoiding the large-scale appearance of defects. Therefore, the absence of silane modification causes the separation factor of the composite membrane to decrease, while the flux increases slightly due to compatibility)
[0098] Comparative Example 3: No Polyethylene Glycol
[0099] (1) Treatment of PVDF bottom membrane: Soak the PVDF bottom membrane with a molecular weight cutoff of 50,000 in a mixed solution of 50% by volume ethanol / water for 5 h, then take it out and rinse it with deionized water, and then place it in deionized water for use.
[0100] (2) Synthesis of layered polyaniline: Add 9.313 g of aniline to 100 mL of 1 M hydrochloric acid, stir for 30 min to mix evenly, record as solution A, and set aside. Take 11.41 g of ammonium persulfate and add it to 100 mL of deionized water, stir for 30 min to dissolve and mix evenly, record as solution B, and set aside. After solution A and solution B are cooled to 0-5°C respectively, quickly pour solution B into solution A. Keep the temperature range between 0-2°C and stir for 1 hour. After the reaction is completed, filter, wash with water and methanol until the filtrate is colorless, and dry in an oven at 80°C for 12 hours to obtain layered polyaniline powder-doped state (doped HCl molecules, layered polyaniline is a type of polyaniline morphology, which is related to the raw material ratio and experimental conditions during synthesis). Then, 5 g of the layered polyaniline powder-doped state was added to 500 mL of 5 wt % ammonia solution, stirred for 24 h, filtered, washed with water and methanol twice in sequence, and dried in an oven at 80° C. for 12 h to obtain layered polyaniline.
[0101] (3) ZIF-71 modified polyaniline: 0.1 g of polyaniline sheet material was added to 50 mL of methanol, and stirred evenly after ultrasonic treatment for 30 min. Then, 1 g of zinc acetate dihydrate was added and stirred for 30 min. The mixture was set aside as solution A. 2.5 g of 4,5-dichloroimidazole was weighed and added to 50 mL of methanol. The mixture was stirred and dissolved and set aside as solution B. Subsequently, solution B was slowly added dropwise to solution A, and the mixture was stirred at room temperature for 120 min. The mixture was filtered and washed with methanol for 3 times, and dried in an oven at 80 °C for 12 h to obtain polyaniline preliminarily modified with ZIF-67. Finally, 0.2 g of the material was added to 50 mL of pre-hydrolysis solution (1 wt% KH590, 2 wt% water, 97 wt% ethanol), stirred at room temperature for 5 h, filtered and washed with water for 3 times, and dried in an oven at 80 °C for 12 h to obtain polyaniline modified with ZIF-71.
[0102] (5) Preparation of template-induced ZIF-71 synthesis-modified polyaniline-based pervaporation membrane: 0.855 g of polydimethylsiloxane (PDMS) was added to 5 mL of n-heptane, and stirred at room temperature for 30 min. Then, 0.103 g of ZIF-71-modified polyaniline powder was added and stirred for 30 min. After that, the steps of stirring for 30 min and ultrasonication for 30 min were repeated for 3 h. Then, 0.0855 g of cross-linking agent tetraethyl orthosilicate was added and stirred for 15 min. Then, 0.0086 g of catalyst dibutyltin dilaurate was added and stirred for 30 min. After standing for 20 min (standing to remove bubbles), 2 mL of the obtained casting solution was taken and a membrane was formed on the above-mentioned PVDF membrane (radius 2 cm disc) by spin coating, and dried in an oven at 80°C for 12 h. Finally, a template-induced ZIF-71 synthesis-modified polyaniline-based pervaporation membrane was obtained.
[0103] The permeation flux of the polyaniline-based pervaporation membrane modified by template-induced ZIF-71 synthesis was 3676 g / m at 40 °C, 1 wt% butanol / water, flow rate 400 mL / min, and filtration vacuum less than 200 Pa. 2 h, and the separation factor is 40.1. (The presence of polyethylene glycol provides continuous active sites for the in-situ growth of MOF. Without polyethylene glycol, MOF cannot grow regularly on the surface of polyaniline, resulting in large-scale agglomeration between fillers. Therefore, there are a large number of interface defects in the composite membrane, and the flux of the membrane increases significantly.)
[0104] Comparative Example 4: No polyaniline
[0105] (1) Treatment of PVDF bottom membrane: Soak the PVDF bottom membrane with a molecular weight cutoff of 50,000 in a mixed solution of 50% by volume ethanol / water for 5 h, then take it out and rinse it with deionized water, and then place it in deionized water for use.
[0106] (2) Silane-modified ZIF-90: 0.1 g of polyethylene glycol was added to 50 mL of methanol, and stirred evenly after ultrasonic treatment for 30 min. Then, 1 g of zinc nitrate hexahydrate was added and stirred for 30 min. The mixture was set aside as solution A. 1.7 g of 2-imidazole carboxaldehyde was weighed and added to 50 mL of N,N-dimethylformamide, and stirred and dissolved. The mixture was set aside as solution B. Subsequently, solution B was poured into solution A, stirred at room temperature for 1 h, filtered and washed with methanol 3 times, and dried in an oven at 80°C for 12 h to obtain ZIF-90. Finally, 0.2 g of this material was added to 50 mL of pre-hydrolysis solution (1 wt% KH550, 2 wt% water, 97 wt% ethanol), stirred at room temperature for 5 h, filtered and washed with water 3 times, and dried in an oven at 80°C for 12 h to obtain silane-modified ZIF-90.
[0107] (3) Preparation of silane-modified ZIF-90-based pervaporation membrane: 0.855 g of polydimethylsiloxane (PDMS) was added to 5 mL of n-heptane, and stirred at room temperature for 30 min. Then, 0.128 g of silane-modified ZIF-90 powder was added and stirred for 30 min. After that, the stirring for 30 min and ultrasonication for 30 min were repeated for 3 h. Then, 0.0855 g of cross-linking agent tetraethyl orthosilicate was added and stirred for 15 min. Then, 0.0086 g of catalyst dibutyltin dilaurate was added and stirred for 30 min. After standing for 20 min (standing to remove bubbles), 2 mL of the obtained casting solution was taken and a membrane was formed on the above-mentioned PVDF membrane (2 cm radius disc) by spin coating, and dried in an oven at 80°C for 12 h. Finally, a silane-modified ZIF-90-based pervaporation membrane was obtained.
[0108] The permeation flux of the obtained silane-modified ZIF-90-based pervaporation membrane at 40°C, 5wt% ethanol / water, flow rate 400mL / min, and filtration vacuum less than 200 Pa was 1906g / m 2 h, and the separation factor is 10.2. (The presence of ZIF-90 alone results in insufficient active sites during silane modification, resulting in low hydrophobicity of the filler; in addition, insufficient compatibility also makes the filler easy to agglomerate.)
[0109] Comparative Example 5: Polydimethylsiloxane film (without filler)
[0110] (1) Treatment of PVDF bottom membrane: Soak the PVDF bottom membrane with a molecular weight cutoff of 50,000 in a mixed solution of 50% by volume ethanol / water for 5 h, then take it out and rinse it with deionized water, dry it in an oven at 60°C for 10 h, and then place it in deionized water for use.
[0111] (2) Preparation of polydimethylsiloxane membrane: 0.855 g of polydimethylsiloxane was added to 5 mL of n-heptane and stirred at room temperature for 30 min; then the steps of stirring for 30 min and ultrasonicating for 30 min were repeated for 3 h; then 0.0855 g of cross-linking agent tetraethyl orthosilicate was added and stirred for 15 min, 0.0086 g of catalyst dibutyltin dilaurate was added and stirred for 30 min, ultrasonicated for 10 min, and allowed to stand for 20 min. Then 2 mL of the obtained casting solution was taken and a membrane was formed on the above-mentioned PVDF membrane (2 cm radius disc) by spin coating, and dried in an oven at 80°C for 12 h to obtain a polydimethylsiloxane pervaporation membrane.
[0112] The permeation flux of the obtained polydimethylsiloxane pervaporation membrane at 40°C and 1 wt% butanol / water was 1239 g / m 2 h, the separation factor is 26; the permeation flux is 1120 g / m at 40 ° C, 5 wt% ethanol / water, flow rate 400 mL / min, and filtration vacuum less than 200 Pa. 2 h, the separation factor is 6.5.
Claims
1. A pervaporation membrane doped with polyaniline-based composite filler modified by template-induced MOFs synthesis, characterized in that: Prepare as follows: S1: Dispersing polyaniline sheets uniformly in deionized water, adding polyethylene glycol solid, reacting at room temperature for 5 to 10 hours, filtering, washing, and drying to obtain polyethylene glycol-modified polyaniline sheets; S2: Add polyethylene glycol-modified polyaniline sheets to solvent A, mix them by ultrasonication, then add metal source and stir evenly, which is recorded as solution A; add ligand to solvent B, stir and dissolve, which is recorded as solution B; pour solution B into solution A, stir and react at room temperature, then filter, wash and dry, then add the obtained solid product to the pre-hydrolysis solution of silane coupling agent, stir and react, then filter, wash and dry to obtain MOFs-modified polyaniline; Wherein, the metal source reacts with the ligand to synthesize MOFs which are in situ grown on the polyethylene glycol-modified polyaniline sheet, and the MOFs are selected from one or more of ZIF-8, ZIF-90, ZIF-67, ZIF-91, ZIF-71, MOF-808, and MOF-199; The pre-hydrolysis solution of the silane coupling agent is composed of: a silane coupling agent, water, and ethanol; the silane coupling agent is selected from one or more of γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, anilinemethyltriethoxysilane, and γ-mercaptopropyltrimethoxysilane; S3: Disperse PDMS evenly in n-heptane, add the polyaniline modified by MOFs obtained in S2, a crosslinking agent, and a catalyst, disperse evenly, and let stand to obtain a casting solution; spin-coat the casting solution on a PVDF membrane, and after drying, obtain the template-induced MOFs synthesis-modified polyaniline-based composite filler-doped pervaporation membrane; Wherein, the crosslinking agent is ethyl orthosilicate and the catalyst is dibutyltin dilaurate.
2. The pervaporation membrane doped with polyaniline-based composite filler modified by template-induced MOFs synthesis as claimed in claim 1, characterized in that: In S1, the mass ratio of the polyaniline sheet to the polyethylene glycol solid is 1:0.1-10.
3. The pervaporation membrane doped with polyaniline-based composite filler modified by template-induced MOFs synthesis as claimed in claim 1, characterized in that: In S2, the mass ratio of the polyethylene glycol-modified polyaniline sheet, the metal source, and the solvent A is 1:5-15:200-1500.
4. The pervaporation membrane doped with polyaniline-based composite filler modified by template-induced MOFs synthesis as claimed in claim 1, characterized in that: In S2, the mass ratio of the ligand to the solvent B is 1:200-1500.
5. The pervaporation membrane doped with polyaniline-based composite filler modified by template-induced MOFs synthesis as claimed in claim 1, characterized in that: In S2, the pre-hydrolysis solution of the silane coupling agent is composed of: silane coupling agent, water, and ethanol in a mass ratio of 0.1-5:1-10:80-99.
6. The pervaporation membrane doped with polyaniline-based composite filler modified by template-induced MOFs synthesis as claimed in claim 1, characterized in that: In S3, the volume mass ratio of n-heptane to PDMS is 2.9-14.6:1, mL / g.
7. The pervaporation membrane doped with polyaniline-based composite filler modified by template-induced MOFs synthesis as claimed in claim 1, characterized in that: In S3, the mass ratio of PDMS, cross-linking agent, catalyst, and MOFs-modified polyaniline is 1:0.05-0.2:0.005-0.03:0.01-0.
3.
8. The pervaporation membrane doped with polyaniline-based composite filler modified by template-induced MOFs synthesis as claimed in claim 1, characterized in that: In S3, when forming the membrane, the amount of the casting solution applied to the PVDF membrane by spin coating is 0.05 to 0.3 g / cm 2 .
9. The pervaporation membrane doped with polyaniline-based composite filler modified by template-induced MOFs synthesis as claimed in claim 1, characterized in that: The preparation method of the polyaniline sheet is as follows: Aniline is dissolved in 0.2-2M hydrochloric acid to obtain an aniline solution; an ammonium persulfate aqueous solution is added to the aniline solution at 0-5°C, stirred for reaction for 0.5-2h, filtered, the filter cake is washed with water and methanol in turn, and dried; the obtained solid is stirred in a 3-15wt% ammonia aqueous solution for reaction for 16-30h, filtered, the filter cake is washed with water and methanol in turn, and dried to obtain the polyaniline sheet; The molar ratio of aniline to ammonium persulfate is 1.5 to 2.8:1; The concentration of aniline in the aniline solution is 0.005 to 2 M; The concentration of the ammonium persulfate aqueous solution is 0.002 to 2M; The volume mass ratio of the ammonia solution to the solid is 50-500:1, mL / g.
10. Use of the pervaporation membrane doped with the polyaniline-based composite filler modified by template-induced MOFs synthesis as claimed in claim 1 in the pervaporation separation of alcohol-water mixture.
Citation Information
Patent Citations
Preparation method of pervaporation membrane for gasoline desulfurization
CN110327781A
Method for preparing PEG / Cu-BTC / PVDF desulfurization mixed matrix membrane by using water-based process
CN110523300A
Polyaniline / polyaryletherketone composite membrane with electrochemical response as well as preparation method and application of polyaniline / polyaryletherketone composite membrane
CN114870638A
Hydrophobic modified material doped composite pervaporation membrane as well as preparation and application thereof
CN116116223A
A forward osmosis membrane
WO2012102678A1